Individualized Education Program (IEP) Mata Pelajaran Kimia untuk Siswa Slow Learner - Rovik, Rovik (PLD UIN Sunan Kalijaga, 2017)
The implementation of inclusive education is one of the government's efforts to providing quality education for all levels of society. However, to date, inclusive education is not working correctly, students with special needs must adapt to learning tailored to their abilities, interests and talents (integration education). As a result, they can not achieve learning objectives, and the worst thing is they will stay class or drop out. A slow learner is one type of disability who received less attention because of its vagueness, so their existence is difficult to identify. IEP (Individualized Education Program) for slow learners can help them achieve progress. Index of inclusion in this research was used to determine the extent of successes of inclusive schools in implementing inclusive education, while the assessment was done to determine the capabilities and needs of the learners.[Siswa slow learner menempati populasi tertinggi untuk siswa berkebutuhan khusus. Sebagai salah satu jenis learning disability, slow learner masih dapat belajar dengan teman sebayanya asalkan guru mempersiapkan program pembelajaran khusus yang telah dimodifikasi dari pembelajaran reguler. Program ini disebut Individualized Education Program (IEP). Penelitian ini mencoba mengembangkan IEP mata pelajaran kimia untuk slow learner, mengidentifikasi komponen yang dibutuhkan dalam menyusun IEP untuk slow learner, dan menganalisis judgement reviewers (guru kimia dan guru pendamping khusus) dan peer reviewers terhadap IEP yang dikembangkan. Hasil penelitian menunjukkan slow learner membutuhkan IEP sebagai dokumen utama panduan guru dalam pembelajaran kimia di kelas. Komponen pengembangan IEP meliputi identitas peserta didik, tim pengembangan dan pelaksana, asesmen yang pernah dilakukan, hambatan dan kekuatan, kebutuhan dan perlakuan, faktor pendukung dan penghambat, rencana perlakuan, dan modifikasi terhadap perangkat pembelajaran kimia reguler]